1995
DOI: 10.1128/jcm.33.11.2850-2855.1995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping of prevalent M serotypes of Streptococcus pyogenes causing invasive disease

Abstract: Reproducible methodologies and a scheme for high-resolution genotyping of Streptococcus pyogenes were defined with respect to a study of six predominant M serotypes causing invasive group A streptococcal disease in the United Kingdom. Serotype reference strains were compared with nine clinical isolates of each serotype from patients with diseases such as pneumonia, puerperal sepsis, toxic shock-like-syndrome, cellulitis, or necrotizing fasciitis. Four enzymes were evaluated for their discriminatory power in 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 20 publications
(23 reference statements)
3
32
1
1
Order By: Relevance
“…When we analyzed the GAS isolates used in this study by PFGE after SmaI digestion, we found that their PFGE patterns agreed with those reported previously (Stanley et al , 1995; Murase et al , 1999) (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…When we analyzed the GAS isolates used in this study by PFGE after SmaI digestion, we found that their PFGE patterns agreed with those reported previously (Stanley et al , 1995; Murase et al , 1999) (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…The emergence of exceptionally virulent strains of these serotypes (Musser et al ., 1991;Cleary et al ., 1992;Musser et al ., 1995) suggested that the increased virulence might be associated with specific genetic elements that could be acquired by horizontal transmission, but no such evidence has been provided. Other studies demonstrated that additional serotypes caused invasive infections (Norgren et al ., 1992;Stanley et al ., 1995;Chaussee et al ., 1996;Cockerill et al ., 1997;Muotiala et al ., 1997). Furthermore, © 2002 Blackwell Publishing Ltd, Molecular Microbiology , 46 , 87-99 the clonal M1T1 strains could be isolated from patients with severe and non-severe invasive infections (Chatellier et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we compared S. pyogenes strains obtained from patients with pharyngitis to those obtained from patients who were asymptomatic over a 7-to 8-year interval. Strain comparisons were performed by using PFGE with SmaI-digested (15) and SfiI-digested (7) chromosomal DNA; PCR-detected speA, speB, or speC genes (11); and biotyping with a commercial biochemical test kit (Rapid ID 32 Strep; bioMeriuex, Marcy-l'Etoile, France) (1). Numerical analysis of SmaI-digested patterns was performed by identifying the proportion of fragments shared by pairs of isolates by the method of Nei and Li (9) (also known as the Dice coefficient of similarity) and calculated as F ϭ 2n xy /(n x ϩ n y ), where n x and n y are the total numbers of fragments from isolates x and y, respectively, and n xy is the number of fragments identical in the two isolates.…”
mentioning
confidence: 99%